1995
DOI: 10.1128/mcb.15.4.2180
|View full text |Cite
|
Sign up to set email alerts
|

Small Maf Proteins Heterodimerize with Fos and May Act as Competitive Repressors of the NF-E2 Transcription Factor

Abstract: The maf oncogene encodes a bZip nuclear protein which recognizes sequences related to an AP-1 site either as a homodimer or as heterodimers with Fos and Jun. We describe here a novel maf-related gene, mafG, which shows extensive homology with two other maf-related genes, mafK and mafF. These three maf-related genes encode small basic-leucine zipper proteins lacking the trans-activator domain of v-Maf. Bacterially expressed small Maf proteins bind to DNA as homodimers with a sequence recognition profile that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
170
0
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(183 citation statements)
references
References 51 publications
6
170
0
7
Order By: Relevance
“…Since it was reported that Maf/Jun heterodimers can bind NF-E2/ AP-1 like sites more e ciently than c-Jun homodimers or Maf homodimers Kerppola and Curran, 1994), NF-E2 activity may be repressed by formation of c-Jun/NF-E2p18 heterodimers that are unable to activate transcription from these sites. Similarly, recent studies have shown that c-Fos can act as a negative regulator of transcription in combination with the small Maf proteins (Kataoka et al, 1995). Although we favor the model of inactive cJun/p18 complexes, two alternative explanations of our results may be considered.…”
Section: C-jun Activates and Nf-e2p18 Inhibits Nf-e2/ap-1 Activity Insupporting
confidence: 66%
See 1 more Smart Citation
“…Since it was reported that Maf/Jun heterodimers can bind NF-E2/ AP-1 like sites more e ciently than c-Jun homodimers or Maf homodimers Kerppola and Curran, 1994), NF-E2 activity may be repressed by formation of c-Jun/NF-E2p18 heterodimers that are unable to activate transcription from these sites. Similarly, recent studies have shown that c-Fos can act as a negative regulator of transcription in combination with the small Maf proteins (Kataoka et al, 1995). Although we favor the model of inactive cJun/p18 complexes, two alternative explanations of our results may be considered.…”
Section: C-jun Activates and Nf-e2p18 Inhibits Nf-e2/ap-1 Activity Insupporting
confidence: 66%
“…Homodimers of small Maf proteins suppress transcription from NF-E2/AP-1 sites in non-erythroid cells (Igarashi et al, 1994). Maf proteins could also heterodimerize with bZip proteins from the Fos/Jun family (Kataoka et al, , 1995Kerpola and Curran, 1994). The Jun/Maf heterodimers have binding speci®cities distinct from those of the Jun/Jun and Maf/Maf homodimers but their transcriptional activity has not yet been reported.…”
mentioning
confidence: 99%
“…As is the case for chicken small Maf proteins (Fujiwara et al, 1993;Kataoka et al, 1995) and mouse MafK (Andrews et al, 1993b;Igarashi et al, 1995a), human MafK and MafG contain a basic domain and a leucine zipper domain, but lack any canonical transactivation domains. The human MafK sequence was established to show 96% and 95% identity with its chicken and mouse counterparts, respectively, while the human MafG sequence showed 94% identity with that of chicken MafG (Figure 3).…”
Section: Isolation and Structures Of The Human Mafk And Mafg Cdna Clonesmentioning
confidence: 96%
“…The large Maf proteins, MafA/L-Maf/ SMaf1 [3][4][5], MafB [6], c-Maf [7], and Nrl [8], contain an acidic domain in their N-termini that acts as a transcriptional activation site. By contrast, the small Maf proteins, MafK, MafF [9], and MafG [10], lack such an acidic domain.…”
mentioning
confidence: 99%